A COMPARATIVE-TYPOLOGICAL ANALYSIS OF GENDER CATEGORIES IN ENGLISH AND UZBEK LINGUISTIC SYSTEMS - Tolibova Shaxzoda Baxtiyorovna (Modern American Journals, 2025)
This study presents a comparative-typological analysis of gender categories in the English and Uzbek linguistic systems, examining their structural, semantic, and functional properties. While English displays a partially grammaticalized gender system reflected mainly in pronouns, lexical items, and certain derivational patterns, Uzbek represents a largely gender-neutral typology with gender distinctions emerging primarily through context, sociocultural markers, and borrowed lexical forms. By applying cross-linguistic comparison and typological classification, the research identifies key areas where the two languages diverge in gender encoding, especially in personal reference, professional titles, kinship terminology, and pragmatic usage. The study also highlights how sociolinguistic factors influence gender representation, showing that ongoing societal changes increasingly shape language practices in both English and Uzbek. The findings contribute to broader discussions on typology, linguistic universals, and the interaction between grammatical structure and social meaning, offering implications for translation studies, language pedagogy, and cross-cultural communication.
Keywords: Gender categories, comparative-typological analysis, english linguistics, uzbek linguistics, gender encoding, cross-linguistic comparison, sociolinguistics, grammatical structure, language typology, gender representation.